Fully revealing equilibria with suboptimal investment - Persons, John C. (Journal of Corporate Finance, 2000)
Myers and Majluf [Myers, S.C., Majluf, N.S., 1984. Corporate financing and investment decisions when firms have information that investors do not have. Journal of Financial Economics 13, 187–221.] showed that mispriced securities can lead managers with private information to invest inefficiently. It seems plausible that this problem would disappear in a fully revealing equilibrium, since information asymmetries are resolved and securities are priced correctly. In fact, Constantinides and Grundy [Constantinides, G.M., Grundy, B.D., 1989. Optimal investment with stock repurchase and financing as signals. Review of Financial Studies 2, 445–465.] claim that, in their model, any fully revealing equilibrium has efficient investment. This claim is incorrect, as infinitely many inefficient equilibria exist for the very example they work out. The inefficient outcomes survive the standard signaling-game equilibrium refinements. There are also examples that have fully revealing equilibria with inefficient investment but none with efficient investment.